2002
DOI: 10.1023/a:1021656607278
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Prenatal stress greatly influences the ability of an individual to manage stressful events in adulthood. Such vulnerability may result from abnormalities in the development and integration of forebrain dopaminergic and glutamatergic projections during the prenatal period. In this study, we assessed the effects of prenatal stress on the expression of selective dopamine and glutamate receptor subtypes in the adult offsprings of rats subjected to repeated restraint stress during the last week of pregnancy. Dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Our findings for NAC dopamine are consistent with previous reports of dopaminergic alterations following either PNS or prenatal glucocorticoid receptor agonist administration that include higher dopamine content and/ or higher dopamine metabolism (metabolite : neurotransmitter ratio) in striatal tissue, increased numbers of tyrosine hydroxylase-positive cells in the ventral tegmental area, and changes in NAC D2 and D3 receptor expression (eg Alonso et al, 1994;Barros et al, 2004;Berger et al, 2002;Diaz et al, 1995;Henry et al, 1995;McArthur et al, 2005). Moreover, the enhanced dopamine response to cocaine produced by PNS is similar to that reported in neonatal isolates (Kehoe et al, 1996;Kosten et al, 2004aKosten et al, , 2003Kosten et al, , 2005Kosten et al, , 2006; see also Howes et al, 2000 for similar results following juvenile isolation) or in rodents subjected to neonatal anoxia (Juarez et al, 2003) in response to other psychomotor stimulant drugs.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainesupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings for NAC dopamine are consistent with previous reports of dopaminergic alterations following either PNS or prenatal glucocorticoid receptor agonist administration that include higher dopamine content and/ or higher dopamine metabolism (metabolite : neurotransmitter ratio) in striatal tissue, increased numbers of tyrosine hydroxylase-positive cells in the ventral tegmental area, and changes in NAC D2 and D3 receptor expression (eg Alonso et al, 1994;Barros et al, 2004;Berger et al, 2002;Diaz et al, 1995;Henry et al, 1995;McArthur et al, 2005). Moreover, the enhanced dopamine response to cocaine produced by PNS is similar to that reported in neonatal isolates (Kehoe et al, 1996;Kosten et al, 2004aKosten et al, , 2003Kosten et al, , 2005Kosten et al, , 2006; see also Howes et al, 2000 for similar results following juvenile isolation) or in rodents subjected to neonatal anoxia (Juarez et al, 2003) in response to other psychomotor stimulant drugs.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainesupporting
confidence: 92%
“…Similar to findings in the NAC, there are alterations in dopamine D2 as well as NMDA and mGluRIII receptors in the PFC following PNS Berger et al, 2002). Moreover, antagonism of dopamine D2 or D1 receptors in the PFC markedly attenuated cocaineprimed reinstatement of cocaine-seeking in both operant (Capriles et al, 2003;Sun and Rebec, 2005) and placeconditioned (Sanchez et al, 2003) models.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainesupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, the PFC is also sensitive to the detrimental effects of exposure to stress, which can impair higher order abilities such as working memory and attention (Arnsten, 2009). Berger et al (2002) found that PS increased DA D2 receptors in the dorsal frontal cortex and medial prefrontal cortex. In addition, Carboni et al (2010) reported that PS reduced NA concentration in the PFC.…”
Section: Discussionmentioning
confidence: 99%
“…This concurrence of outcomes is notable, given that the greatest proportion of children with elevated blood lead (PbB) levels reside in low socioeconomic status communities, where prenatal stress is also considered to be highly prevalent (Gavin et al, 2012; Lancaster et al, 2010; Miszkurka et al, 2012), consistent with the interpretation that these are co-occurring risk factors in the human environment. That elevated PbB levels and PS should lead to common adverse outcomes including cognitive and attention deficits, likely reflects the fact that both Pb exposure and prenatal stress also significantly modify the functions of the central nervous system’s (CNS) fronto-striatal/mesocorticolimbic circuits, and its associated monoamine (dopamine and serotonin)-glutamate balance (Barros et al, 2004; Berger et al, 2002; Cory-Slechta et al, 1998; 1999; Martinez-Tellez et al, 2009; Rossi-George et al, 2011; Virgolini et al, 2008), that have been shown to subserve these behavioral domains (Dalley et al, 2008; Dalley and Roiser, 2012; Kim and Lee, 2011; Luman et al, 2010; Pattij and Vanderschuren, 2008; Tripp and Wickens, 2009). …”
Section: Introductionmentioning
confidence: 99%